Enhancing reading comprehension through make a match with control board at SDN 112/II Purwo Bakti - Cut Dara Nadia Ladiski; Aprizan Aprizan; Elvima Nofrianni (Curricula: Journal of Curriculum Development, 2025)
Reading comprehension is a fundamental skill essential for elementary school students; however, many still struggle to understand the content of texts. This condition was also identified at SDN 112/II Purwo Bakti, where most fourth-grade students had not yet achieved the minimum mastery criteria. This study aimed to enhance students’ reading comprehension skills through the application of the cooperative learning model, "Make a Match," assisted by a control board. The research was conducted in the form of Classroom Action Research (CAR), carried out in two cycles consisting of planning, implementation of action, observation, and reflection. The participants consisted of 35 fourth-grade students, and data were collected through observation sheets and reading comprehension tests. The findings revealed a significant improvement in both the learning process and students’ outcomes. Students became more active, motivated, and engaged in learning activities, and their ability to understand texts improved. The implementation of the Make a Match model assisted by a control board proved effective in creating an interactive and enjoyable learning environment that enhanced students’ reading comprehension skills at the elementary school level. learning environment, thereby enhancing students’ motivation, active participation, and reading comprehension skills.   Abstrak Kemampuan membaca pemahaman merupakan keterampilan dasar yang esensial bagi peserta didik sekolah dasar, namun kenyataannya masih banyak peserta didik mengalami kesulitan dalam memahami isi bacaan. Kondisi tersebut juga ditemukan di SDN 112/II Purwo Bakti, di mana sebagian besar peserta didik kelas IV belum mencapai kriteria ketuntasan minimal. Penelitian ini bertujuan untuk meningkatkan keterampilan membaca pemahaman peserta didik melalui penerapan model pembelajaran kooperatif Make a Match berbantuan media papan kontrol. Penelitian ini dilaksanakan dalam bentuk Penelitian Tindakan Kelas (PTK) selama dua siklus dengan tahapan perencanaan, pelaksanaan tindakan, observasi, dan refleksi. Subjek penelitian terdiri dari 35 peserta didik kelas IV, dengan data diperoleh melalui observasi dan tes membaca pemahaman. Hasil penelitian menunjukkan adanya peningkatan yang signifikan baik dalam proses pembelajaran maupun hasil belajar. Peserta didik menjadi lebih aktif, termotivasi, dan terlibat dalam kegiatan pembelajaran, serta mampu memahami isi bacaan secara lebih baik. Penerapan model Make a Match berbantuan papan kontrol terbukti efektif dalam menciptakan suasana belajar yang interaktif dan menyenangkan sehingga mampu meningkatkan keterampilan membaca pemahaman peserta didik sekolah dasar. Kata Kunci: make a match; membaca pemahaman; papan kontrol; sekolah dasar